PENGEMBANGAN MEDIA OPERMAN (ORGAN PERNAPASAN MANUSIA) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SDN SERTAJAYA 05 - Risni Wahyuni; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Student learning motivation needs to be increased again due to low interest in learning, student activeness and concentration in learning activities, besides that there is still a lack of variation in class learning. This study aims to increase student learning motivation in the subject of IPAS human respiratory system material. This research uses the type of R&D research with the ADDIE development model. The feasibility test was carried out by validators, namely for material expert validation 92%, for language validation 92% and media validation 95%. With the three validator scores, it shows that the media is suitable for testing. The 96% teacher response results prove that the media is practical to use. The results of the distribution of learning motivation questionnaires obtained a percentage of 95% with a very effective category. Based on the results of the study, it can be concluded that operman media can increase student learning motivation.